2019
DOI: 10.1038/s41422-019-0231-y
|View full text |Cite
|
Sign up to set email alerts
|

BH3-only proteins target BCL-xL/MCL-1, not BAX/BAK, to initiate apoptosis

Abstract: It has been widely accepted that mitochondria-dependent apoptosis initiates when select BH3-only proteins (BID, BIM, etc.) directly engage and allosterically activate effector proteins BAX/BAK. Here, through reconstitution of cells lacking all eight pro-apoptotic BH3-only proteins, we demonstrate that all BH3-only proteins primarily target the anti-apoptotic BCL-2 proteins BCL-xL/MCL-1, whose simultaneous suppression enables membrane-mediated spontaneous activation of BAX/BAK. BH3-only proteins' apoptotic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 45 publications
6
94
0
8
Order By: Relevance
“…It was reported that MTCH2 could facilitate the recruitment of the truncated BID to mitochondria (24). BID could indirectly activate BAX/BAK and thus allowing them to undergo unimpeded, spontaneous activation in the mitochondrial outer membrane, leading to apoptosis initiation (25). Studies have suggested that, when activated, Bak and Bax, create discontinuity or pores in the outer mitochondrial membrane, to mediate the release of Cytochrome C (26).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that MTCH2 could facilitate the recruitment of the truncated BID to mitochondria (24). BID could indirectly activate BAX/BAK and thus allowing them to undergo unimpeded, spontaneous activation in the mitochondrial outer membrane, leading to apoptosis initiation (25). Studies have suggested that, when activated, Bak and Bax, create discontinuity or pores in the outer mitochondrial membrane, to mediate the release of Cytochrome C (26).…”
Section: Discussionmentioning
confidence: 99%
“…While one would assume that the setting, in which the activation of Bax by BH3-only proteins is required (for the sake of simplicity we will refer to this as to 'activation-requiring' Bax) reflects the situation observed in mammalian cells, recent experiments with knock-out mammalian cells simultaneously lacking all eight genes encoding for BH3-only proteins indicated that even in mammalian cells Bax may be activated by the inhibition of antiapoptotic proteins only when BH3-only proteins are absent [48,49]. Dispensability of BH3-only proteins for Bax activation, thus, appears to correlate with the behaviour of the 'constitutively active' version Bax in yeast.…”
Section: Bax and Bak Activationmentioning
confidence: 99%
“…These studies have shown the Bcl-2 family consists of two phylogenetically distinct groups of proteins: those that share the Bcl-2 fold [90,93] that are either prosurvival or proapoptotic and the proapoptotic intrinsically disordered 'BH3-only' proteins, that bear only the BH3 motif [9]. The BH3-only proteins are upregulated in response to diverse apoptotic stimuli [94] and their principal role is to antagonize the prosurvival proteins [9], but apoptosis also occurs in their absence [95]. Notwithstanding the conservation in the Bcl-2 family, there are substantial differences in Bcl-2-regulated apoptosis mechanisms.…”
Section: Introductionmentioning
confidence: 99%